Living On the Edge: Memory, Urban Transformation, And the Legacy of Berlin Wall العيش على الحافة: الذاكرة، التحول الحضري، وإرث جدار برلين - Hebah Moanis Hatem (Journal of Urban Research, 2025)
Berlin’s urban landscape, shaped by the legacy of the Berlin Wall, serves as a compelling narrative of division, resilience, and reunification. This research investigates how Berlin’s former border zones have evolved into vibrant urban spaces that preserve historical memory while addressing contemporary urban needs. Central to this study is the question: How do historically divided urban environments transform and reconfigure their identity in the post-reunification era? Adopting a qualitative, interpretative methodology, the study integrates narrative inquiry, autoethnographic fieldwork, and archival research, structured by a thematic analytical framework. It combines diachronic and synchronic perspectives to examine both the historical trajectories and present-day social-spatial dynamics of selected sites. Data was collected through site visits, field notes, photographs, and documentary archives, and was systematically coded and interpreted using a six-dimensional framework addressing memory, identity, architecture, and public engagement. The findings illustrate Berlin’s multifaceted strategies for urban transformation, blending preservation and innovation through adaptive reuse, participatory design, artistic expression, and commemorative practices. The study offers valuable insights for cities seeking to integrate memory and identity into inclusive and sustainable urban development.